1992
DOI: 10.1017/s0954102092000440
|View full text |Cite
|
Sign up to set email alerts
|

The stratigraphical palynology of the Kotick Point and Whisky Bay formations, Gustav Group (Cretaceous), James Ross Island

Abstract: Palynomorph assemblages are reported from the Kotick Point and Whisky Bay formations in west and north-west James Ross Island, Antarctic Peninsula. The microfloras, particularly the dinoflagellate cyst florules, indicate an Aptian to early/mid Albian age for the Kotick Point Formation and a mid Albian to Turonian age for the Whisky Bay Formation on the basis of comparison with records from other Southern Hemisphere localities. The ages adduced broadly corroborate those previously derived from macrofaunas. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 10 publications
0
17
0
2
Order By: Relevance
“…Angiosperm diversity during the thermal maximum includes morphotypes similar to many living families, which are indicative of tropical and subtropical climates at high latitudes during the mid to Late Cretaceous (Francis et al, 2008). In addition, clay minerals (Dingle and Lavelle, 1998), fossil wood (Poole et al, 2005), and angiosperm pollen deposits in Turonian sediments (Keating et al, 1992) all suggest a warm period and correspond very well to the Cretaceous thermal maximum (Francis et al, 2008). After the thermal peak, the climate begins to cool for a period (based on the fossil wood record), but warms again during the Palaeocene and early Eocene (Kennett and Stott, 1991;Zachos et al, 1993Zachos et al, , 1994Zachos et al, , 2008Katz et al, 1999;Norris and Ro¨hl, 1999;Peters and Sloan, 2000;Francis and Poole, 2002;Poole et al, 2005;Rose, 2006;Francis et al, 2008).…”
Section: When and Where Mantodea Evolvedmentioning
confidence: 99%
“…Angiosperm diversity during the thermal maximum includes morphotypes similar to many living families, which are indicative of tropical and subtropical climates at high latitudes during the mid to Late Cretaceous (Francis et al, 2008). In addition, clay minerals (Dingle and Lavelle, 1998), fossil wood (Poole et al, 2005), and angiosperm pollen deposits in Turonian sediments (Keating et al, 1992) all suggest a warm period and correspond very well to the Cretaceous thermal maximum (Francis et al, 2008). After the thermal peak, the climate begins to cool for a period (based on the fossil wood record), but warms again during the Palaeocene and early Eocene (Kennett and Stott, 1991;Zachos et al, 1993Zachos et al, , 1994Zachos et al, , 2008Katz et al, 1999;Norris and Ro¨hl, 1999;Peters and Sloan, 2000;Francis and Poole, 2002;Poole et al, 2005;Rose, 2006;Francis et al, 2008).…”
Section: When and Where Mantodea Evolvedmentioning
confidence: 99%
“…In other Antarctic paleoclimate studies evidence for strong warmth at this time was found by Dingle and Lavelle (1998) in their analyses of clay minerals and from analysis of fossil woods . This warm peak may have also been the trigger for the expansion of the angiosperms in the Antarctic, represented by a marked increased abundance of angiosperm pollen in Turonian sediments (Keating et al, 1992). On a global scale this corresponds to the Cretaceous thermal maximum, from about 100-80 Ma, reported from many sites (e.g., Clark and Jenkyns, 1999;Huber et al, 2002), and possibly attributed to rising atmospheric CO 2 levels due to a tectonically driven oceanographic event in the opening of the equatorial Atlantic gateway (Poulsen et al, 2003).…”
Section: Francis Figmentioning
confidence: 99%
“…Sub se quent stud ies of microfossils from the James Ross Is land re gion have clearly shown the po ten tial for es tab lish ing biostratigraphic frame works us ing foraminifera, di a toms, silicoflagellates and palynomorphs (e.g., Askin, 1988;Har wood, 1988;Huber, 1988). Other pre lim i nary stud ies on James Ross and sur rounding is lands have also shown the po ten tial of palynomorphs for lo cal and re gional biostratigraphical cor re la tion (e.g., Askin, 766 Lilian Švábenická, Radek Vodrážka and Daniel Nývlt 1983; Olivero and Palamarczuk, 1987;Baldoni and Me dina, 1989;Keating, 1992;Keating et al, 1992;Rid ing et al, 1992;Rid ing and Crame, 2002). Cre ta ceous nannofossils from the Ant arc tic area in clud ing the Falkland Pla teau are men tioned by Wind (1979), Huber et al (1983), Thomas et al (1990), Wei and Thierstein (1991), Watkins et al (1996) and Lees (2002).…”
Section: Previous Biostratigraphic Studiesmentioning
confidence: 99%